PENGEMBANGAN MBCT BERBASIS NILAI-NILAI GURINDAM MELAYU RIAU UNTUK MENGATASI DISTORSI KOGNITIF PADA MAHASANTRI - Sinta Kurnia Sari; Mudafiatun Isriyah; Weni Kurnia Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Cognitive distortion is a negative thought pattern that can disrupt mental health and emotional balance, particularly in Islamic boarding schools (pesantren) environments where spiritual and academic demands must be met. This cognitive distortion causes individuals to neglect consideration, focusing solely on negative aspects and failing to think rationally. Consequently, individuals perceive an inaccurate and chaotic reality. Some students, particularly students residing in Islamic boarding schools, experience cognitive distortions due to the need to meet spiritual and academic demands. This study aims to develop Mindfulness-Based Cognitive Therapy (MBCT) integrated with the values ​​of the Riau Malay Gurindam as a cultural approach to addressing cognitive distortions in Islamic boarding school students. The values ​​of Gurindam, particularly those from Raja Ali Haji's Gurindam Dua Belas, were chosen because they contain moral messages, self-awareness, and spiritual reflection relevant to the principles of mindfulness and cognitive therapy. The method used in this study is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The study subjects were Islamic boarding school students (pesantren) who exhibited symptoms of cognitive distortions such as negative thinking, overgeneralization, and self-balancing. Preliminary results indicate that integrating Gurindam values ​​can strengthen the contemplative dimension of MBCT, increase self-awareness, and reduce the frequency and intensity of cognitive distortions. This study recommends the importance of a local cultural approach in psychological interventions to increase effectiveness and emotional closeness in Islamic boarding school-based populations.